2006
DOI: 10.1158/0008-5472.can-05-3186
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Activating Factor Induces Up-regulation of Antiapoptotic Factors in a Melanoma Cell Line through Nuclear Factor-κB Activation

Abstract: In this study, we investigated the influence of plateletactivating factor (PAF) on the induction of apoptosisregulating factors in B16F10 melanoma cells. PAF increased the expression of mRNA and the protein synthesis of antiapoptotic factors, such as Bcl-2 and Bcl-xL, but did not increase the expression of the proapoptotic factor, Bax. A selective nuclear factor-KB (NF-KB) inhibitor, parthenolide, inhibited the effects of PAF. Furthermore, PAF inhibited etoposide-induced increases in caspase-3, caspase-8, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…NF-κB is both a downstream effector of TLR signaling and it is an upstream regulator of TLR4 expression, making this transcription factor a central molecule in inflammatory regulation. PAF has been shown to activate NF-κB in enterocytes in vivo [52] and in several other cell types in tissue culture [33], [53]. In light of PAF's ability to activate NF-κB and given that the TLR4 promoter contains NF-κB binding sites [29], it is not surprising that we observed a dependence of PAF-induced TLR4 gene expression on NF-κB activation.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…NF-κB is both a downstream effector of TLR signaling and it is an upstream regulator of TLR4 expression, making this transcription factor a central molecule in inflammatory regulation. PAF has been shown to activate NF-κB in enterocytes in vivo [52] and in several other cell types in tissue culture [33], [53]. In light of PAF's ability to activate NF-κB and given that the TLR4 promoter contains NF-κB binding sites [29], it is not surprising that we observed a dependence of PAF-induced TLR4 gene expression on NF-κB activation.…”
Section: Discussionmentioning
confidence: 58%
“…To begin addressing the possible signaling mechanisms that may underlie PAF-mediated regulation of TLR expression, we evaluated the potential roles of two major transcription factors regulated by PAF, STAT3 [32] and NF-κB [33], both of which have been implicated in TLR4 signaling and/or gene expression regulation [34]. We first wished to verify that PAF stimulation activated STAT3 in IEC, as was shown before in COS-7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…SKmel37 cells were cultivated in vitro and treated with cisplatin (5  μ M) and WEB2086 (5  μ g/mL) for 24 h, in the presence or absence of PAF (3  μ mol/L, based on experimental delineation in Seo et al [9]). WEB2086 was initially added to the culture medium, and after 30 minutes, cisplatin and/or PAF were added.…”
Section: Resultsmentioning
confidence: 99%
“…Despite contrary reports [6], recent data have shown that PAFR activation induces upregulation of antiapoptotic gene products, such as Bcl-2, thus attenuating the cytotoxic effect of chemotherapeutic agents [9]. In this scenario, specific PAFR antagonists may have a potential effect in blocking protective tumour responses and potentiating chemotherapy [1719].…”
Section: Introductionmentioning
confidence: 99%
“…PAF also plays a significant role in oncogenic transformation (17), anti-apoptosis (18), metastasis (19) and angiogenesis in several types of cancers (20). Transgenic mice overexpressing PAFR displayed proliferative disorders and melanocytic tumors (21).…”
Section: Introductionmentioning
confidence: 99%